Association of Smoking Status With Health-Related Outcomes After Percutaneous Coronary Intervention. (May 2015) - Jang, Jae-Sik; Buchanan, Donna M.; Gosch, Kensey L.; Jones, Philip G.; Sharma, Praneet K.; Shafiq, Ali; Grodzinsky, Anna; Fendler, Timothy J.; Graham, Garth; Spertus, John A.
<x xml:space="preserve">Abstract</x> Background— Patients who smoke at the time of percutaneous coronary intervention (PCI) would ideally have a strong incentive to quit, but most do not. We sought to compare the health status outcomes of those who did and did not quit smoking after PCI with those who were not smoking before PCI. Methods and Results— A cohort of 2765 PCI patients from 10 US centers were categorized into never, past (smoked in the past but had quit before PCI), quitters (smoked at time of PCI but then quit), and persistent smokers. Health status was measured with the disease-specific Seattle Angina Questionnaire and the EuroQol 5 dimensions, adjusted for baseline characteristics. In unadjusted analyses, persistent smokers had worse disease-specific and overall health status when compared with other groups. In fully adjusted analyses, persistent smokers showed significantly worse health-related quality of life when compared with never smokers. Importantly, of those who smoked at the time of PCI, quitters had significantly better adjusted Seattle Angina Questionnaire angina frequency scores (mean difference, 2.73; 95% confidence interval, 0.13–5.33) and trends toward higher disease specific (Seattle Angina Questionnaire quality of life mean difference, 1.97; 95% confidence interval, −1.24 to 5.18), and overall (EuroQol 5 dimension visual analog scale scores mean difference, 2.45; 95% confidence interval, −0.58 to 5.49) quality of life when compared with persistent smokers at 12 months. Conclusions— Smokers at the time of PCI have worse health status at 1 year than those who never smoked, whereas smokers who quit after PCI have less angina at 1 year than those who continue smoking.